Involvement of Mitogen-Activated Protein Kinase Pathways in Interleukin-8 Production by Human Monocytes and Polymorphonuclear Cells Stimulated with Lipopolysaccharide or Mycoplasma fermentans Membrane Lipoproteins - Marie, Christelle (American Society for Microbiology, 1999)
Interleukin-8 (IL-8) is a chemokine that belongs to the α-chemokine or CXC subfamily and is produced by a wide variety of human cells, including monocytes and polymorphonuclear cells (PMN). IL-8 is secreted in response to inflammatory stimuli, notably bacterial products such as lipopolysaccharide (LPS), but little is known about the mechanisms by which these agents mediate IL-8 induction. In this report, we show that Mycoplasma fermentans lipid-associated membrane proteins (LAMPf) induce the production of high levels of IL-8 by THP-1 (human monocyte) cells and PMN at the same extent as LPS. It was previously demonstrated that stimulation of monocytic cells with either LPS or LAMPf led to a series of common downstream signaling events, including the activation of protein tyrosine kinase and of mitogen-activated protein kinase cascades. By using PD-98059 and SB203580, two potent and selective inhibitors of MEK1 (a kinase upstream of ERK1/2) and p38, respectively, we have demonstrated that both ERK1/2 and p38 cascades play a key role in the production of IL-8 by monocytes and PMN stimulated with bacterial fractions.